Pengaruh Produk Asuransi, Personal Selling dan Kualitas Pelayanan Terhadap Minat Beli Asuransi Produk Life Plan PT Asuransi Jiwa Sequis Life Medan - Dhita Adriani Rangkuti; Marvin Zimka; Chynthia Chynthia; Calvin Kristio; Calvin Tanady (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Research done in PT Asuransi Jiwa Sequis Life Medan. The purpose of the Research is to test and analyze the influence of insurance products, personal selling and the quality of pelayananterhadap interest in purchasing insurance products life plan. The phenomenon that occurs interest in purchasing insurance products life plan decreased due to insurance products, personal selling and service quality. Population of 167 consumers and the number of sampelgsebanyak 118 consumers and for testing the validity and reliability of as many as 30 customers outside of the study sample. The sampling technique used is random sampling sampling. The partial and simultaneous Insurance Products, Personal Selling and Service Quality have a positive and signfiikan against the Interest of the Insurance Product Life Plan Insurance PT Sequis Life Medan.